Method for deeply removing mineral impurities in quartz sand

Through the method of strengthening quenching and acid leaching of low-temperature roasting and ethanol-deionized aqueous solution combined with acid leaching, the problem of difficult removal of mineral impurities in non-high-quality quartz mineral sources is solved, and the depth purification of high-purity quartz sand and effective reduction of lattice impurities are achieved.

CN119797373AActive Publication Date: 2025-04-11KUNMING UNIV OF SCI & TECH

Patent Information

Application Number
CN202510044129.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-04-11
Estimated Expiration
2045-01-10

AI Technical Summary

Technical Problem

There are a large number of mineral impurities in non-high-quality quartz mineral sources, causing metal elements to diffuse into the quartz matrix during the roasting process, forming difficult-to-remove crystal lattice impurities, reducing the limit of quartz sand purification.

Method used

The method of strengthening quenching of low-temperature calcination combined with ethanol-deionized aqueous solution is used to reduce the calcination temperature to 400-870℃, and the mineral impurities in quartz sand are removed through primary and secondary acid leach to minimize the diffusion behavior of metal impurities.

Benefits of technology

The depth removal of mineral impurities in quartz sand is achieved, and the upper limit of purification of high-purity quartz sand with SiO2 purity higher than 99.995% is improved, the formation of lattice impurities is reduced, and the purity and quality of quartz sand is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119797373A_ABST
    Figure CN119797373A_ABST
Patent Text Reader

Abstract

The invention relates to a method for deeply removing mineral impurities in quartz sand, and belongs to the technical field of quartz mineral purification. Natural quartz minerals are directly crushed and screened to obtain quartz sand; performing primary acid leaching treatment on the quartz sand to remove mineral impurities on the surface layer or near the surface layer; heating the primary acid-leached quartz sand to a preset temperature (400-870 DEG C) at a constant speed so as to realize low-temperature roasting treatment, immediately taking out the quartz sand after reaching the preset temperature, and directly adding the quartz sand into an ethanol-deionized water solution for strengthening quenching, so that the quartz matrix generates cracks from inside to outside from inclusion mineral impurities; and carrying out secondary acid leaching treatment on the strengthened and quenched quartz sand to deeply remove inclusion mineral impurities in the quartz so as to obtain the high-purity quartz sand. According to the method, mineral impurities in the quartz sand are deeply removed through the purification process of primary acid leaching, low-temperature roasting, reinforced quenching and secondary acid leaching, and the high-purity quartz sand with the silicon dioxide purity higher than 99.995% can be prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for deeply removing mineral impurities in quartz sand, belonging to the technical field of quartz mineral purification. Background Art

[0002] Quartz sand with SiO2 content greater than 99.99% is called high-purity quartz sand. It has good chemical stability and thermal stability, excellent optical and electrical properties, and is widely used in high-tech fields such as silicon photovoltaics, semiconductors, optoelectronics, and aerospace. However, with the depletion of natural crystal granite pegmatite minerals, limited high-quality quartz sand production resources can no longer meet the growing demand for high-purity quartz sand. The preparation of high-purity quartz sand using non-high-quality mineral sources as raw materials has become an inevitable trend in the development of the high-purity quartz sand industry.

[0003] There are a lot of mineral impurities in non-high-quality quartz ore sources, which can be divided into surface mineral impurities and internal inclusion mineral impurities according to their existence forms. Internal inclusion mineral impurities can be divided into inclusion minerals located at the grain boundary and inclusion minerals inside the crystal according to their occurrence positions. During the roasting process, the metal elements in the mineral impurities will diffuse into the quartz matrix, forming lattice impurities that are difficult to remove, resulting in incomplete removal of mineral impurities and reducing the purification limit of quartz sand.

[0004] In the existing quartz sand impurity removal process, in order to fully expose the mineral inclusions inside the quartz, the roasting temperature used is above 900°C and the holding time is above 2 hours, followed by quenching with an aqueous solution or a salt solution. Although the higher roasting temperature and longer holding time promote the exposure of mineral impurities, it is inevitable that the metal elements in the mineral impurities diffuse into the quartz matrix to form lattice impurities. Therefore, although the existing high-temperature roasting and quenching process can promote the purification of quartz sand to a certain extent, the content of metal impurities in the obtained quartz sand is still high. Summary of the invention

[0005] In view of the problem that metal elements in mineral impurities in the preparation of high-purity quartz sand using non-high-quality quartz ore as raw material will diffuse into the quartz matrix, forming lattice impurities that are difficult to remove, resulting in incomplete removal of mineral impurities and reducing the purification limit of quartz sand, the present invention proposes a method for deeply removing mineral impurities in quartz sand, which comprehensively considers the exposure of internal mineral impurities and the diffusion of metal elements in mineral impurities during the purification process of quartz sand. While ensuring that the mineral impurities inside the quartz are fully exposed, the diffusion behavior of metal impurities is minimized to obtain high-purity quartz sand with SiO2 purity higher than 99.995%.

[0006] A method for deeply removing mineral impurities in quartz sand, the specific steps are as follows:

[0007] (1) crushing and screening natural quartz minerals to obtain quartz sand;

[0008] (2) adding quartz sand into the acid solution A in the reactor to carry out an acid leaching to remove surface or near-surface mineral impurities, thereby obtaining primary acid-leached quartz sand;

[0009] (3) the acid-leached quartz sand is heated to a preset temperature at a uniform speed to achieve low-temperature roasting treatment, and is taken out immediately after reaching the preset temperature to obtain low-temperature roasted quartz sand; the preset temperature is 400-870° C. to reduce the diffusion of metal elements in the internal inclusion minerals into the quartz matrix to form lattice impurities; the combination of a lower roasting temperature and no need for heat preservation can minimize the diffusion behavior of metal elements in mineral impurities, greatly reduce the probability of formation of lattice impurities that are difficult to remove, and provide the possibility for deep removal of mineral impurities in quartz;

[0010] (4) Low-temperature roasted quartz sand is immediately added to an ethanol-deionized water solution for enhanced quenching, so that cracks are generated from the inside to the outside of the quartz matrix from the inclusion mineral impurities, and the solid-liquid separation is performed to obtain enhanced quenched quartz sand; the use of ethanol-deionized water solution greatly increases the extreme cold effect of the quartz surface, creating favorable conditions for the exposure of the inclusion mineral impurities inside the quartz;

[0011] (5) The reinforced quenched quartz sand is added to the acid solution B in the reactor for secondary acid leaching to deeply remove the mineral impurities in the quartz inclusions, separate the solid and the liquid, and wash the solid with ultrapure water and ethanol in turn and dry it to obtain high-purity quartz sand.

[0012] The primary acid leaching process must be performed before the low-temperature roasting and quenching process, that is, before roasting, the mineral impurities on the surface of the quartz must be completely removed, and the mineral impurities in the inclusions at the grain boundaries inside the quartz must be removed as much as possible to avoid the metal elements in the surface mineral impurities and the mineral impurities in the inclusions at the grain boundaries from diffusing into the quartz matrix during the roasting process to form lattice impurities that are difficult to remove.

[0013] Preferably, the SiO2 content in the natural quartz mineral in step (1) is not less than 95%; and the particle size of the quartz sand is 74 to 350 μm.

[0014] Preferably, the acid solution A in step (2) is a binary or polybasic mixed acid consisting of hydrochloric acid and at least one organic acid, and the organic acid is oxalic acid, acetic acid, citric acid, propionic acid, tartaric acid, malic acid or succinic acid.

[0015] More preferably, the hydrochloric acid concentration in the acid solution A is 3-12 wt.%, and the organic acid concentration is 0.5-5 wt.%.

[0016] More preferably, the acid leaching temperature is 150-350°C, the pressure is 0.48-16.5MPa, and the acid leaching time is 0.5-6h. Since high temperature and high pressure act on the grain boundaries at the same time, the grain boundaries are opened, so that the mineral impurities at some grain boundaries are exposed and directly react with the acid solution to be removed. The deep removal of surface minerals and some inclusion minerals at the grain boundaries avoids the metal elements contained in the surface mineral impurities and some inclusion mineral impurities at the grain boundaries from entering the quartz lattice in the subsequent roasting process, forming lattice impurities that are difficult to remove, thereby ensuring the final impurity removal effect.

[0017] Preferably, the uniform heating rate in step (3) is 5-15°C / min, so as to ensure that the overall temperature of the quartz is uniform after reaching the set temperature, and the temperature difference range is controlled within ±5°C.

[0018] Preferably, the ethanol concentration in the ethanol-deionized water solution in step (4) is 5 to 50 wt.%, and the strengthening quenching temperature is -2 to -40°C. The quartz matrix is ​​cracked from the inside to the outside at the inclusion mineral impurities. Due to the difference in thermal expansion coefficients between quartz and its internal inclusion mineral impurities, the thermal decomposition of impurity minerals, the extreme cold effect produced by quenching, and the volume effect produced by quartz crystal transformation, the four factors jointly generate internal stress, causing the quartz matrix to crack from the inside to the outside at the impurities, exposing the grain boundary inclusion mineral impurities and the inclusion mineral impurities inside the grains, providing favorable conditions for the deep removal of the inclusion mineral impurities inside the quartz.

[0019] Preferably, the acid solution B in step (5) is a hydrochloric acid solution with a concentration of 5 to 15 wt.%. During the secondary acid leaching process, the hydrochloric acid solution directly contacts the exposed mineral impurities inside the quartz, thereby achieving the purpose of deeply removing the impurities inside the quartz.

[0020] More preferably, the secondary acid leaching temperature in step (5) is 150-350° C. and the time is 0.5-6 h.

[0021] The beneficial effects of the present invention are:

[0022] (1) The present invention deeply removes impurities on the surface of quartz sand and impurities in some grain boundary inclusions by acid leaching once, and then calcines the quartz sand, which directly avoids the diffusion of metal elements in mineral impurities on the surface of quartz and some grain boundary mineral impurities into the quartz matrix during the calcination process to form difficult-to-remove lattice impurities. Compared with the existing process, the lattice impurity content in the product can be reduced, and the upper limit of quartz sand purification can be increased;

[0023] (2) The roasting temperature of the present invention is reduced to a range of 400-870°C. During the roasting process, the difference in thermal expansion coefficients between the metal impurities inside the quartz and the quartz matrix, the decomposition of impurity minerals, the huge temperature difference between the inside and outside of the quartz during the quenching process, and the volume effect caused by the quartz crystal transformation will all cause internal stress in the quartz. Under the combined effect of the above four factors, a roasting temperature within the range of 400-870°C is sufficient to allow the quartz matrix to produce abundant cracks from the inside out at the mineral impurities, providing a direct channel for the removal of impurities during the secondary acid leaching process;

[0024] (3) The present invention eliminates the heat preservation process during the roasting process and directly performs quenching after reaching the set temperature. This can minimize the diffusion of metal elements in the mineral impurities in the quartz inclusions during the roasting process while ensuring that the quartz surface is cooled suddenly due to the temperature reduction and the internal stress of the quartz is increased. This reduces the probability of forming lattice impurities and can achieve the effect of deeply removing the mineral impurities in the inclusions in the quartz sand during the secondary acid leaching process.

[0025] (4) The quenching solution used in the present invention is a 5-50wt.% ethanol solution, which can reduce the quenching temperature to -40°C, greatly increasing the temperature difference between the surface and the interior of the quartz. The specific heat capacity of ethanol (the specific heat capacity of ethanol at 20°C is 2.3×10 3 J·kg -1 ℃ -1 ) is less than the specific heat capacity of water (the specific heat capacity of water at 20°C is 4.2×10 3 J·kg -1 ℃ -1 ), so using ethanol solution as a quenching agent can make the quartz surface have a higher temperature difference. In addition, the boiling point of ethanol is 78.3°C, which is lower than the boiling point of water by 100°C. Therefore, the quenching solution used in this application can ensure that the quenching agent evaporates in time after absorbing a large amount of heat, which greatly increases the heat exchange efficiency. Compared with other quenching solutions, it can further increase the temperature difference between the quartz surface and the interior, and increase the internal stress of the quartz particles; therefore, the present invention does not need to use the volume effect at 870°C to achieve the slow crystal transformation process of 16% tridymite, and can achieve the purpose of fully exposing the mineral impurities inside the quartz. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a process flow chart of the present invention. DETAILED DESCRIPTION

[0027] The present invention is further described in detail below in conjunction with specific implementation modes, but the protection scope of the present invention is not limited to the described contents.

[0028] Embodiment 1: A method for deeply removing mineral impurities in quartz sand, characterized in that the specific steps are as follows:

[0029] (1) crushing and screening natural quartz mineral with a purity of 95% to obtain quartz sand with a particle size of 80 to 150 μm;

[0030] (2) adding quartz sand to the acid solution A (a ternary mixed acid of hydrochloric acid-organic acid (acetic acid and citric acid)) in the reactor, and performing an acid leaching for 1 hour at a temperature of 200° C. and a pressure of 1.4 MPa to remove surface or near-surface mineral impurities, thereby obtaining primary acid-leached quartz sand; the acid solution A contains 10 wt.% of hydrochloric acid, 2 wt.% of acetic acid, and 4 wt.% of citric acid;

[0031] (3) The acid-leached quartz sand is uniformly heated to a preset temperature (870° C.) at a heating rate of 10° C. / min to achieve low-temperature calcination, and is immediately taken out after reaching the preset temperature (870° C.) to obtain low-temperature calcined quartz sand;

[0032] (4) the low-temperature roasted quartz sand is immediately added to an ethanol-deionized water solution (ethanol concentration is 20 wt.%), and subjected to enhanced quenching at a temperature of -10°C, so that cracks are generated from the inside to the outside of the quartz matrix from the inclusion mineral impurities, and the solid-liquid separation is performed to obtain enhanced quenched quartz sand;

[0033] (5) adding the strengthened quenched quartz sand to the acid solution B (hydrochloric acid with a concentration of 9 wt.%) in the reactor, and performing secondary acid leaching at a temperature of 180° C. for 2 h to deeply remove the mineral impurities in the inclusions inside the quartz, and performing solid-liquid separation. The solid was washed twice with ultrapure water, and then washed three times with ethanol, and dried to obtain high-purity quartz sand;

[0034] The SiO2 content and impurity element content in the high-purity quartz sand of this embodiment were analyzed by ICP-MS, and the purity of the high-purity quartz sand was 99.9953%.

[0035] Embodiment 2: A method for deeply removing mineral impurities in quartz sand, characterized in that the specific steps are as follows:

[0036] (1) crushing and screening natural quartz mineral with a purity of 99% to obtain quartz sand with a particle size of 100 to 200 μm;

[0037] (2) adding quartz sand to the acid solution A (binary mixed acid of hydrochloric acid and acetic acid) in the reactor, and performing an acid leaching for 4 hours at a temperature of 150° C. and a pressure of 0.48 MPa to remove surface or near-surface mineral impurities, thereby obtaining primary acid-leached quartz sand; the hydrochloric acid concentration in the acid solution A is 12 wt.%, and the organic acid (acetic acid) concentration is 5 wt.%;

[0038] (3) the acid-leached quartz sand is uniformly heated to a preset temperature (600° C.) at a heating rate of 5° C. / min to achieve low-temperature calcination, and is immediately taken out after reaching the preset temperature (600° C.) to obtain low-temperature calcined quartz sand;

[0039] (4) the low-temperature roasted quartz sand is immediately added to an ethanol-deionized water solution (ethanol concentration is 35 wt.%), and subjected to enhanced quenching at a temperature of -20°C, so that cracks are generated from the inside to the outside of the quartz matrix from the inclusion mineral impurities, and the solid-liquid separation is performed to obtain enhanced quenched quartz sand;

[0040] (5) adding the strengthened quenched quartz sand to the acid solution B (hydrochloric acid with a concentration of 5 wt.%) in the reactor, and performing secondary acid leaching at a temperature of 350° C. for 4 h to deeply remove the mineral impurities in the inclusions inside the quartz, and performing solid-liquid separation. The solid was washed 3 times with ultrapure water, and then washed 2 times with ethanol, and dried to obtain high-purity quartz sand;

[0041] The SiO2 content and impurity element content in the high-purity quartz sand of this embodiment were analyzed by ICP-MS, and the purity of the high-purity quartz sand was 99.9981%.

[0042] Embodiment 3: A method for deeply removing mineral impurities in quartz sand, characterized in that the specific steps are as follows:

[0043] (1) crushing and screening natural quartz mineral with a purity of 97% to obtain quartz sand with a particle size of 100 to 200 μm;

[0044] (2) adding quartz sand to the acid solution A (a mixed acid of hydrochloric acid-organic acid (acetic acid and oxalic acid)) in the reactor, and performing an acid leaching for 1 hour at a temperature of 300° C. and a pressure of 8.58 MPa to remove surface or near-surface mineral impurities, thereby obtaining a primary acid-leached quartz sand; the acid solution A has a hydrochloric acid concentration of 3 wt.%, an acetic acid concentration of 5 wt.%, and an oxalic acid concentration of 5 wt.%;

[0045] (3) the acid-leached quartz sand is uniformly heated to a preset temperature (800° C.) at a heating rate of 5° C. / min to achieve low-temperature calcination, and is immediately taken out after reaching the preset temperature (800° C.) to obtain low-temperature calcined quartz sand;

[0046] (4) the low-temperature roasted quartz sand is immediately added to an ethanol-deionized water solution (ethanol concentration is 35 wt.%), and subjected to enhanced quenching at a temperature of -23°C, so that cracks are generated from the inside to the outside of the quartz matrix from the inclusion mineral impurities, and the solid-liquid separation is performed to obtain enhanced quenched quartz sand;

[0047] (5) adding the strengthened quenched quartz sand to the acid solution B (hydrochloric acid with a concentration of 10 wt.%) in the reactor, and performing secondary acid leaching at a temperature of 230° C. for 6 h to deeply remove the mineral impurities in the inclusions inside the quartz, and performing solid-liquid separation. The solid was washed 3 times with ultrapure water, and then washed 2 times with ethanol, and dried to obtain high-purity quartz sand;

[0048] The SiO2 content and impurity element content in the high-purity quartz sand of this embodiment were analyzed by ICP-MS, and the purity of the high-purity quartz sand was 99.9968%.

[0049] Embodiment 4: A method for deeply removing mineral impurities from quartz sand, characterized in that the specific steps are as follows:

[0050] (1) crushing and screening natural quartz mineral with a purity of 96% to obtain quartz sand with a particle size of 150 to 250 μm;

[0051] (2) adding quartz sand to the acid solution A (a ternary mixed acid of hydrochloric acid-organic acid (succinic acid and tartaric acid)) in the reactor, and performing an acid leaching for 0.5 h at a temperature of 250° C. and a pressure of 4 MPa to remove surface or near-surface mineral impurities, thereby obtaining primary acid-leached quartz sand; the acid solution A has a hydrochloric acid concentration of 8 wt.%, a succinic acid concentration of 0.5 wt.%, and a tartaric acid concentration of 2 wt.%;

[0052] (3) the acid-leached quartz sand is uniformly heated to a preset temperature (400° C.) at a heating rate of 15° C. / min to achieve low-temperature calcination, and is immediately taken out after reaching the preset temperature (700° C.) to obtain low-temperature calcined quartz sand;

[0053] (4) the low-temperature roasted quartz sand is immediately added to an ethanol-deionized water solution (ethanol concentration is 46 wt.%), and subjected to enhanced quenching at a temperature of -30°C, so that cracks are generated from the inside to the outside of the quartz matrix from the inclusion mineral impurities, and the solid-liquid separation is performed to obtain enhanced quenched quartz sand;

[0054] (5) adding the strengthened quenched quartz sand to the acid solution B (hydrochloric acid with a concentration of 10 wt.%) in the reactor, and performing secondary acid leaching at a temperature of 270° C. for 5 h to deeply remove the mineral impurities in the inclusions inside the quartz, and performing solid-liquid separation. The solid was washed with ultrapure water for 4 times, and then washed with ethanol for 2 times, and dried to obtain high-purity quartz sand;

[0055] The SiO2 content and impurity element content in the high-purity quartz sand of this embodiment were analyzed by ICP-MS, and the purity of the high-purity quartz sand was 99.9961%.

[0056] Embodiment 5: A method for deeply removing mineral impurities from quartz sand, characterized in that the specific steps are as follows:

[0057] (1) crushing and screening natural quartz mineral with a purity of 98% to obtain quartz sand with a particle size of 300 to 350 μm;

[0058] (2) adding quartz sand to the acid solution A (binary mixed acid of hydrochloric acid and malic acid) in the reactor, and performing acid leaching for 1 hour at a temperature of 280° C. and a pressure of 4.47 MPa to remove surface or near-surface mineral impurities, thereby obtaining primary acid-leached quartz sand; the hydrochloric acid concentration in the acid solution A is 6 wt.%, and the organic acid (malic acid) concentration is 1 wt.%;

[0059] (3) The primary acid-leached quartz sand is uniformly heated at a heating rate of 8°C / min to a preset temperature (650°C) to achieve low-temperature calcination, and is immediately taken out after reaching the preset temperature (650°C) to obtain low-temperature calcined quartz sand;

[0060] (4) the low-temperature roasted quartz sand is immediately added to an ethanol-deionized water solution (ethanol concentration is 50 wt.%), and subjected to enhanced quenching at a temperature of -40°C, so that cracks are generated from the inside to the outside of the quartz matrix from the inclusion mineral impurities, and the solid-liquid separation is performed to obtain enhanced quenched quartz sand;

[0061] (5) adding the strengthened quenched quartz sand to the acid solution B (hydrochloric acid with a concentration of 12 wt.%) in the reactor, and performing secondary acid leaching at a temperature of 190° C. for 4 h to deeply remove the mineral impurities in the inclusions inside the quartz, and performing solid-liquid separation. The solid was washed 3 times with ultrapure water, and then washed 3 times with ethanol, and dried to obtain high-purity quartz sand;

[0062] The SiO2 content and impurity element content in the high-purity quartz sand of this embodiment were analyzed by ICP-MS, and the purity of the high-purity quartz sand was 99.9995%;

[0063] Examples 1 to 5 The SiO2 content and impurity element content in high-purity quartz sand were analyzed by ICP-MS, and the results are shown in Table 1:

[0064] Table 1 SiO2 content and impurity element content in high purity quartz sand of Examples 1 to 5

[0065] <![CDATA[SiO2 content (%)]]> Total content of metal impurities (μg / g) Example 1 99.9953 47 Example 2 99.9981 29 Example 3 99.9968 32 Example 4 99.9961 39 Example 5 99.9990 10

[0066] The purity of the high-purity quartz sand SiO2 prepared in Examples 1 to 5 is not less than 99.995%, and can reach up to 99.9995%.

[0067] The specific implementation modes of the present invention are described in detail above, but the present invention is not limited to the above implementation modes, and various changes can be made within the knowledge scope of ordinary technicians in this field without departing from the purpose of the present invention.

Claims

1. A method for deeply removing mineral impurities from quartz sand, characterized in that: The specific steps are as follows: (1) crushing and screening natural quartz minerals to obtain quartz sand; (2) adding quartz sand into the acid solution A in the reactor to carry out an acid leaching to remove surface or near-surface mineral impurities, thereby obtaining primary acid-leached quartz sand; (3) the acid-leached quartz sand is heated uniformly to a preset temperature to achieve low-temperature calcination, and is taken out immediately after reaching the preset temperature to obtain low-temperature calcined quartz sand; the preset temperature is 400-870° C.; (4) low-temperature roasted quartz sand is immediately added to an ethanol-deionized water solution for enhanced quenching, so that cracks are generated from the inside to the outside of the quartz matrix from the inclusion mineral impurities, and the solid-liquid separation is performed to obtain enhanced quenched quartz sand; (5) The reinforced quenched quartz sand is added to the acid solution B in the reactor for secondary acid leaching to deeply remove the mineral impurities in the quartz inclusions, separate the solid and the liquid, and wash the solid with ultrapure water and ethanol in turn and dry it to obtain high-purity quartz sand.

2. The method for deep removal of mineral impurities in quartz sand according to claim 1, characterized in that: Step (1) The SiO2 content in the natural quartz mineral is not less than 95%; the particle size of the quartz sand is 74 to 350 μm.

3. The method for deep removal of mineral impurities in quartz sand according to claim 1, characterized in that: The acid solution A in step (2) is a binary or polybasic mixed acid consisting of hydrochloric acid and at least one organic acid, wherein the organic acid is oxalic acid, acetic acid, citric acid, propionic acid, tartaric acid, malic acid or succinic acid.

4. The method for deep removal of mineral impurities in quartz sand according to claim 3, characterized in that: The concentration of hydrochloric acid in the acid solution A is 3-12 wt.%, and the concentration of organic acid is 0.5-5 wt.%.

5. The method for deep removal of mineral impurities in quartz sand according to claim 3 or 4, characterized in that: The primary acid leaching temperature is 150-350°C, the pressure is 0.48-16.5MPa, and the acid leaching time is 0.5-6h.

6. The method for deep removal of mineral impurities in quartz sand according to claim 1, characterized in that: The uniform heating rate in step (3) is 5 to 15°C / min.

7. The method for deep removal of mineral impurities in quartz sand according to claim 1, characterized in that: Step (4) The ethanol concentration in the ethanol-deionized water solution is 5 to 50 wt.%, and the enhanced quenching temperature is -2 to -40°C.

8. The method for deep removal of mineral impurities in quartz sand according to claim 1, characterized in that: The acid solution B in step (5) is a hydrochloric acid solution with a concentration of 5 to 15 wt.%.

9. The method for deep removal of mineral impurities in quartz sand according to claim 8, characterized in that: The secondary acid leaching temperature in step (5) is 150-350° C. and the time is 0.5-6 h.

Citation Information

Patent Citations

  • Preparation method of high-purity quartz sand

    CN111892059A

  • Method for preparing 4N7-grade high-purity quartz sand from muscovite type granite quartz

    CN116605883A

  • Chemical deep purification method for high-purity quartz sand and high-purity quartz sand

    CN118047388A

  • Method for low-carbon efficient extraction of high-purity sio 2 from high-silicon hematite tailings

    WO2024036664A1

Cited By

  • Preparation process of high-purity quartz sand powder based on purification and sintering synergistic effect

    CN122725280A